Comparative audit of blood transfusion during war and peace in Sarajevo. - Lavy, C; Keene, G; Begovic, M; Strauss, S (1996)
A comparative study was made between 146 patients receiving blood transfusion at the State Hospital, Sarajevo, in a 3-month period of peace (group 1) and 250 patients receiving transfusions in a 3-month period of war (group 2). In group 1, trauma accounted for only 7% of transfusions while it accounted for 99% in group 2. The threshold for transfusion was increased in war and the mean pretransfusion haematocrit in group 2 was 21%, compared with 27% in group 1 (P < 0.001). Less blood was also transfused per patient in war with a mean transfusion volume of 1.1 units in group 2 compared with 2.6 units in group 1 (P < 0.001). The reasons and justification for such a conservative transfusion practice in a besieged city are discussed.